Tun Mahathir conferred Honorary Doctorate In Automotive Engineering - UMP, PNC
Universiti Malaysia Pahang (UMP), for the first time, conferred an Honorary Doctorate in Automotive Engineering to former Prime Minister Yang Amat Berbahagia Tun Dr. Mahathir Mohamad in recognition to his continuous contribution to developing the nation’s automotive industry.